Floristic and phytosociology of weeds in pastures in Maranhão State, Northeast Brazil - Costa, Jaílson; Mesquita, Mário Luiz (Revista Ciência Agronômica, 2016)
Knowledge of weed floristic composition and phytosociology are key factors for improving weed management in pastures. Information on weed species that occur in pastures in Northeast Brazil, particularly in Maranhão State is very limited. It is, therefore, important, to search for information to help farmers to control weeds in livestock farming. This paper describes the weed flora diversity and community structure parameters, including density, frequency, abundance and importance value for each weed species found in five pastures of same age and management in Maranhão State, Northeast Brazil. The weed survey was carried out using a wooden frame (80 cm x 30 cm) placed randomly on the soil surface 30 times in each pasture (n = 150). Weeds were pulled out, separated by species and counted. The weed flora was represented by 996 individuals, from nine families, 15 genera and 19 species. Weed density within pastures was of 44.3 plants m-2. The weed flora was dominated by species of the Cyperaceae and Poaceae families. The most important weed species based on Importance Value were Eragrostis ciliaris (IV = 32.97), Cyperus rotundus (IV = 31,95), Cyperus luzulae (IV = 27,50), Cyperus sphacelatus (IV = 27,42), Pycreus lanceolatus (IV = 27,33) Cyperus haspan (IV = 25,72) and Eleusine indica (IV = 23,49). Weed diversity, based on Shannon Diversity Index was very high (H’ = 4.37 nats ind-1). Our results could lead to improved weed management in pastures in Maranhão State, Northeast Brazil.